Mind-controlled transgene expression by a wireless-powered optogenetic designer cell implant - Folcher, Marc; Oesterle, Sabine; Zwicky, Katharina; Thekkottil, Thushara; Heymoz, Julie; Hohmann, Muriel; Christen, Matthias; Daoud El-Baba, Marie; Buchmann, Peter; Fussenegger, Martin (Nature communications, 2014)
Synthetic devices for traceless remote control of gene expression may provide new treatment opportunities in future gene- and cell-based therapies. Here we report the design of a synthetic mind-controlled gene switch that enables human brain activities and mental states to wirelessly programme the transgene expression in human cells. An electroencephalography (EEG)-based brain–computer interface (BCI) processing mental state-specific brain waves programs an inductively linked wireless-powered optogenetic implant containing designer cells engineered for near-infrared (NIR) light-adjustable expression of the human glycoprotein SEAP (secreted alkaline phosphatase). The synthetic optogenetic signalling pathway interfacing the BCI with target gene expression consists of an engineered NIR light-activated bacterial diguanylate cyclase (DGCL) producing the orthogonal second messenger cyclic diguanosine monophosphate (c-di-GMP), which triggers the stimulator of interferon genes (STING)-dependent induction of synthetic interferon-β promoters. Humans generating different mental states (biofeedback control, concentration, meditation) can differentially control SEAP production of the designer cells in culture and of subcutaneous wireless-powered optogenetic implants in mice. Brain–machine interfaces offer the possibility of controlling prosthetic devices using changes in brain activity. Folcher et al. couple such a system wirelessly to an optogenetic implant in mice to control expression of a transgene, demonstrating its potential for mind-controlled drug delivery.